2011
DOI: 10.1186/1471-2458-11-165
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum behaviour as predictor of weight change from before pregnancy to one year postpartum

Abstract: BackgroundPostpartum weight retention affects many women and increases the risk of becoming overweight. The research objective was to study modifiable factors contributing to weight change at one year postpartum.MethodsIn this prospective cohort, postpartum behavior, such as physical activity, sedentary behavior, sleep, and intake of total energy, total fat and saturated fatty acids of 118 Dutch women were assessed in 2003/2004 by self-report at 6 weeks, 6 and 12 months postpartum. Mean postpartum scores were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 35 publications
10
88
0
7
Order By: Relevance
“…Moreover, physical activity is in some (15), but not all (29) studies associated with a reduced risk of excessive gestational weight gain, and lower postpartum weight retention at 1 year (30). In accord with our findings, hours of TV viewing, has previously been associated with increased weight retention 1 year after delivery (10) and with a higher 6-year weight gain among middle-aged women (31).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, physical activity is in some (15), but not all (29) studies associated with a reduced risk of excessive gestational weight gain, and lower postpartum weight retention at 1 year (30). In accord with our findings, hours of TV viewing, has previously been associated with increased weight retention 1 year after delivery (10) and with a higher 6-year weight gain among middle-aged women (31).…”
Section: Discussionsupporting
confidence: 82%
“…In postpartum samples, high levels of total energy intake has been associated with increased risk of weight retention (Oken, Taveras, Popoola, Rich-Edwards, & Gillman, 2007); however, quality of food may also be an important predictor of post-birth weight change (Althuizen, Van Poppel, De Vries, Seidell, & Van Mechelen, 2011). For example, high intake of trans fats (Oken et al, 2007) and saturated fats (Althuizen et al, 2011) predict substantial PWR; however, there are presently very few studies that specifically investigate the influence of dietary quality on PWR.…”
Section: Dietary Qualitymentioning
confidence: 98%
“…It showed that the frequency of women with a level of weight retention considered excessive during the postpartum period was high, reaching 15%, (14) which was also observed in international research. (15) However, as demonstrated in the initial model of this study, gender was not associated with EW, individually. This finding should be investigated more accurately in future studies, forecasting the possible relationship between gender and children.…”
Section: Discussionmentioning
confidence: 84%